Prevalence of Bacterial Infection Isolated from Blood Cultures and Patterns of Antibiotic Resistance and Sensitivity in Pediatrics Department of ZMC during (2019-2020) - Ben Hasan, Etab Shaban; Lmrabet, Ashur Mohamed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
Background: Sepsis is a damage of tissues resulting from the body response to the infection, and considered the second major cause of mortality among neonates and leads to more than one million neonates every year. Sepsis is a body response to an infection leads to damage the tissues, and considered the second major cause of mortality among neonates and leads to more than one million neonates every year. The aim of this study was to retrospectively identify the microorganisms isolated from blood cultures that cause sepsis in Zliten Medical Center(ZMC), which is important for the treatment of patients. A blood culture is the most common test for diagnosis and treatment. Method: A retrospective cross-sectional study of all bacteria isolated in blood cultures obtained from the patients in the department neonatal and pediatric of the (ZMC). Manually review records in the microbiology lab at (ZMC) for information on the types of bacteria that cause bloodstream infections in newborns and children, the most common pathogens and antibiotic sensitivity of each pathogen. Results: During the study period, 32 positive samples were collected. K. pneumonia 8(25%), A. baumannii 6(18.75%), E. coli 4(12.5%), S. aureus 3 (9.37%), and P. aeruginosa 2(6.25%) were the commonly isolated organisms causing neonatal sepsis, followed by other microorganisms. All these microorganisms were highly resistant to common antibiotics like Ciprofloxacin and Gentamicin (53%), Imipenem (47%), Cefoxitin (41%), and least resistance to Amikacin (13%) and Colistin (3%). were the most sensitivity to Amikacin (56%), Nitrofurantoin (31%), Colistin (19%), Imipenem and Levofloxacin (16%), and least sensitivity to Meropenem and Gentamicin (6%). Conclusions: In this study, most common isolated microorganisms were K. pneumoniae. In addition, it should be kept in mind may be cause of sepsis is A. baumannii, E. coli, S. aureus and other microorganisms. The microorganisms isolated were highly resistant to common antibiotics Ciprofloxacin and Gentamicin and least resistance to Colistin, and most sensitivity to Amikacin, and least sensitivity to Meropenem and Gentamicin.